Lineamientos generales de una política criminal de los derechos humanos. Desde una postura personalista realista (2005)
Criminal Political as a type of justice policy should be understood as that which configures the penal system, a contiguration oriented by a very clear decisiveness by the punitive power. This decisiveness in none other than the legitimacy –for the peripheral countries– of Penal Law, that is. “Of the ves and when of the juridical–penal sanctions to typical conducts” and thus ol the punitive power.Thiscontiguration of the penal system may be achieved in an uncouth manner, such as that expounded by the totalitarian criminal policies: or in a very elaborated manner, as it occurs with the liberal criminal policies, where it is sought after to elabórate a liberal penal system as wéll as a liberal penal law, a fact which by itself should be critical and limiting, yet through one or the other, the punitive power becomes legitímate.